KOMPETENSI DAN KINERJA KADER PENDAMPING KELUARGA DALAM PROGRAM PENCEGAHAN STUNTING: KAJIAN PERSPEKTIF MANAJEMEN SUMBER DAYA MANUSIA STRATEGIS DI KECAMATAN DAKOPEMAN KABUPATEN TOLITOLI - Mirayanti Mirayanti; Fakhruddin Kurnia M; Ramla Ilham Darise (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
Stunting remains a serious problem in human development in Indonesia as it affects the quality of human resources, cognitive development, and children’s productivity in the future. The Family Assistance Program for stunting prevention, initiated by BKKBN and the Ministry of Health, positions community cadres as the frontline actors in prevention efforts. This study aims to analyze the competencies and performance of family assistance cadres as well as the strategic human resource management (HRM) factors that influence their effectiveness. This research employed a descriptive qualitative approach in Dakopemean Subdistrict, Tolitoli Regency, Central Sulawesi. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using the Miles and Huberman model. The results show that cadre competencies include knowledge of nutrition and child growth, communication skills, and the use of reporting technology. Major challenges identified were limited training, inadequate ICT facilities, and inconsistent incentives. The effectiveness of assistance increased when supported by strategic HRM elements such as continuous training, feedback-based supervision, fair incentives, and non-material recognition. In conclusion, enhancing cadre competencies and implementing HRM policies aligned with program objectives are key to the success of stunting prevention at the family level.